Legal Protection of Eigentumsverponding Deeds in the Context of Inheritance Rights - Titin Hartati; Boy Nurdin (Journal of Social Research, 2024)
The strength of the eigendom verponding deed in the context of inheritance rights, as well as the legal protection provided to the rights holders. The eigendom verponding deed serves as valid proof of land ownership and has significant legal implications, especially in the inheritance process. This research explores the legal protection available for holders of eigendom verponding deeds and the legal consequences arising from such deeds in the context of inheritance rights. It has been found that this deed can function as strong evidence in the inheritance process; however, it is also vulnerable to disputes if not supported by adequate documentation. This study also discusses efforts that eigendom verponding rights holders can undertake to safeguard and protect their inheritance rights. These efforts include land rights registration, conversion of rights into ownership rights, and compliance with applicable legal provisions to ensure that inheritance rights are recognized and not lost. This research emphasizes the importance of a deep understanding of the rights and obligations of eigendom verponding deed holders, as well as the need for consultation with legal advisors to minimize the risk of losing rights.